Acute and dramatic saxophone penis - Carlota Gutiérrez García-Rodrigo; Lidia Maroñas-Jimenéz; Diana Menis; Hugo Larráin; Lara Angulo Martínez (Wolters Kluwer Medknow Publications, 2015)
We present a case of intense genital swelling because of a hereditary angioedema. This rare disease should be included in the differential diagnosis of acute and asymptomatic genital edema, because it may prevent future potentially life-threatening episodes of visceral angioedema.